Screening for Antimicrobial Activities in Endophytes Isolated From Melastoma malabathricum in Kota Samarahan, Sarawak - Jenisah, Gubau @ Jomiun (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study was carried out to determine the presence of antimicrobial activities in endophytes isolated from stem of Melastoma malabathricum in Kota Samarahan, Sarawak. A total of 20 fungal endophytes were successfully isolated from the stems and after initial observation only six isolates which were 1b, 1c, 2a, 2b, 2c and 2d were tentatively recognize as different species. All the six were screened on three different media which were Potato Dextrose Agar (PDA), V8 juice (V8) and Czapek Dox Agar (CDA). In the preliminary screening, fungal colonies 1b, 1c, 2c and 2d were active against the test bacteria consisting of Enterobacter aeruginosa, Escherichia coli, Salmonella typhii and Staphylococcus aureus. Two endophytes namely isolates 1c and 2d with higher potential of antimicrobial product were chosen for further analysis. However, in the antifungal test, zone of inhibition was not observed between isolates 1c and 2d against Fusarium sp. Extraction of secondary metabolites from endophyte isolates 1c and 2d was done using methanol. Methanol extract 1c and 2d were tested against test bacteria which were Enterobacter aeruginosa, Escherichia coli, Salmonella typhii and Staphylococcus aureus. There were two methodologies involve during antimicrobial screening for methanol extracts namely Standardization Volume method and Minimum Inhibitory Concentration (MIC). Only methanol extract 1c formed zone of inhibition against Escherichia coli, Salmonella typhii and Staphylococcus aureus in Standardization Volume method. Meanwhile, zone of inhibition was not observed with both extract methanol of isolates 1c and 2d in MIC test. In morphological studies, endophytic fungi isolated 1c showed morphology of Zygomycetes spp, the fungus displayed as mycelium sparse, slender, branches with no septate. Isolate 2d displayed characteristic of Choanephora in which showed white mycelium, conidiophores and branches at the apex. The study support that endophytes isolated from M. malabathricum could be useful sources of novel antibiotics for treatment in future.